A review of GaN RF devices and power amplifiers for 5G communication applications - Hao Lu; Meng Zhang; Ling Yang; Bin Hou; Rafael Perez Martinez; Minhan Mi; Jiale Du; Longge Deng; Mei Wu; Srabanti Chowdhury; Xiaohua Ma; Yue Hao (Fundamental Research)
In the emerging 5G and beyond 5G (B5G) era, the spotlight is sharply focused on the power amplifier, a critical component with stringent specification requirements that dictates the performance of the transmitter. The gallium nitride (GaN) device, with its superior inherent properties, is surfacing as a front-runner for power amplifier applications. The increasing demand for high frequency, high linearity, and cost-effective GaN power amplifiers is driven by anticipated traffic surges and the need for extensive 5G deployment. This paper offers a thorough review and future perspective on research developments in RF GaN device technology. It encompasses critical issues in advanced device and circuit technology, with a focus on high frequency, high linearity, cost-effective GaN-on-Si high electron mobility transistors (HEMTs), and compact modeling. This work aims to serve as a guide for the utilization of GaN HEMTs in 5G communication applications.